2007
DOI: 10.1590/s0101-20612007000300014
|View full text |Cite
|
Sign up to set email alerts
|

Postharvest respiratory activity and changes in some chemical constituents during maturation of yellow mombin (Spondias mombin) fruit

Abstract: Mature fruit from the yellow mombin (Spondias mombin) was monitored for its respiration activity. Mature green fruit from the yellow mombin was stored in closed glass chambers and the concentration of oxygen and carbon dioxide at the end of a six hour respiration period was determined. At the same interval of time, the lid of the chamber was opened for air renewal. The increase in carbon dioxide and decrease in oxygen concentration demonstrated that the fruit was climacteric. The maximum liberation of CO 2 54.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
1
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 4 publications
0
9
1
5
Order By: Relevance
“…Sampaio et al (2007), evaluated the respiration of mombin fruits and found SS contents of 9.1 (ripened green) to 13.7 °Brix (maximum climacteric).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sampaio et al (2007), evaluated the respiration of mombin fruits and found SS contents of 9.1 (ripened green) to 13.7 °Brix (maximum climacteric).…”
Section: Resultsmentioning
confidence: 99%
“…However, this fruit high perishability is one of the critical issues that hinder its feasibility throughout its production chain (MOREIRA et al, 2002). Therefore, the understanding of the biological and environmental processes involved in this fruit post-harvest deterioration is necessary and can be used as a basis to develop technologies to increase its post-harvest life and maintain the fruit quality (SAMPAIO et al, 2007).…”
Section: Mombinmentioning
confidence: 99%
“…Sampaio et al (2007) observaram, após 186 horas da colheita, através do monitoramento do processo respiratório de frutos de cajá, a liberação máxima de CO 2 de 54,2 mL.kg -1 .h -1 , quando o fruto alcançou qualidade máxima, iniciando em seguida a senescência. Isto resultou em uma vida útil de prateleira dos frutos de apenas 8 dias.…”
Section: Introductionunclassified
“…Fruit pulp density increase with fruit maturity at the yellow ripe stage (81.58%) compared to the green stages of development (75.71-79.41%). Sampaio et al (2007) investigated the respiratory activity and associated changes in chemical constituents during maturation of chili plums. They reported that the pre-climacteric was marked by the initial production of 24.4 ml kg -1 h -1 CO 2 and initial oxygen absorption of 25.5 ml kg -1 h -1 .…”
Section: Culinary Uses Nutritional Value and Health Benefitsmentioning
confidence: 99%